2017
DOI: 10.1521/pedi_2016_30_269
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Course of Borderline Personality Disorder: A Prospective 10-Year Follow-Up Study

Abstract: The aim of this prospective study was to expand previously reported evidence on the 10-year clinical and functional course of borderline personality disorder (BPD) in a Spanish sample. Participants diagnosed with BPD were assessed at baseline and at 10-year follow-up to evaluate BPD symptomatology and other relevant clinical measures, suicidal behavior, dimensional personality traits, Axis I and II comorbidity, use of mental health resources, and psychosocial functioning. At the 10-year follow up, significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 40 publications
3
46
0
2
Order By: Relevance
“…However, like prior studies, Alvarez-Tomás et al also observed a reduction in general activity (functioning) and social life despite a marked improvement in psychiatric symptoms of BDP such as emotional dysregulation, affective instability, and impulsivity (10).…”
Section: Introductionsupporting
confidence: 62%
“…However, like prior studies, Alvarez-Tomás et al also observed a reduction in general activity (functioning) and social life despite a marked improvement in psychiatric symptoms of BDP such as emotional dysregulation, affective instability, and impulsivity (10).…”
Section: Introductionsupporting
confidence: 62%
“…The course of BPD from adolescence to adulthood is characterized by a symptomatic switch from predominantly symptoms of affective dysregulation, impulsivity, and suicidality to maladaptive interpersonal functioning and enduring functional impairments, with subsequent periods of remission and relapse of the full categorical BPD diagnosis, i.e., meeting the threshold of at least five out of nine DSM-criteria for BPD [ 16 •, 32 , 33 ]. Longitudinal studies show a general decrease of full BPD diagnoses from young to middle adulthood [ 34 , 35 ]. However, remission of the categorical BPD diagnosis is commonly followed by relapse, and almost half of BPD patients never recover fully, both socially and vocationally [ 35 , 36 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%
“…BPD in young adulthood predicts a host of negative outcomes across the life span, including mood, anxiety, eating and substance use disorders, increased risk for physical illnesses and medical care, reduced quality of life, and reduced life expectancy [ 39 , 42 45 ]. As a consequence, many BPD patients never manage to fully participate in society [ 34 , 46 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%
“…The hours of formal therapy fluctuated between 60 and over 600 h, the latter reported by the MBT trial [20]. Among naturalistic studies, two studies followed up samples who initially participated in a clinical trial, although treatment subgroups were not individually studied at follow-up [10,13]. Besides, three naturalistic studies informed of treatment use during follow-up in general terms.…”
Section: Treatment Interventionsmentioning
confidence: 99%